The 2014 European Parliamentary Elections in Slovenia: Hardly and Novelty - Krasovec, Alenka; Dezelan, Tomaz (Political Preferences, 2014)
In the article the main characteristics of the European Parliament elections in 2014 in relation to the characteristics of the both previous elections to the Parliament were analysed. First, the legal framework is presented, followed by the presentation of candidate lists. As it is frequently the case, the authors for the analysis employed the analytical framework presented by Reif and Schmitt (1980). Following the framework, it is obvious the elections in Slovenia again demonstrated many elements of the second-order elections framework, for example in terms of the turnout, success of the governmental parties, success of small parties, as well as almost complete absence of party programmes, Euroscepticism and European topics in the campaign. Since several important domestic events happened just before the EP elections (e.g. resignation of the government at the beginning of May and the fact the leader of the biggest opposition party was by the court found guilty of corruption activity and sent to the prison at the end of April) such developments did not come as a big surprise. Key words: Slovenia, European Parliament, elections, Euroscepticism